2020
DOI: 10.1021/acssuschemeng.0c06911
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyurea Thermoplastics through a Nonisocyanate Route Using CO2 and Aliphatic Diamines

Abstract: The transformation of CO2 can alleviate environmental problems and promote sustainable development. We prepared polyureas (PUas) from CO2 and diamines via an isocyanate-free route. PUas synthesized by the copolymerization of CO2 with 1,6-hexamethylene diamine (HMDA) and 1,12-diaminododecane (DAD) presented superior mechanical properties compared to the ones from CO2 with either DAD or HMDA alone. The PUas contained DAD and HMDA segments in the main polymer chains, and hydrogen bonds were formed between DAD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“… a Number average molecular weight and dispersities were estimated from SEC with the THF eluent at 40 °C relative to poly­(methyl methacrylate) standards. b The crystallinity X c was calculated from DSC by dividing Δ H m = 19.3 J/g with Δ H m,100% = 219 J/g of DAD as crystallinity was caused by the addition of DAD. The Δ H m,100% of DAD was estimated by interpolation from the Δ H m,100% of 1,12-diaminododecane and 1,6-hexamethylene diamine c The crystallinity X c was calculated from WAXS by using the deconvolution method to estimate the area of the amorphous and crystalline portions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Number average molecular weight and dispersities were estimated from SEC with the THF eluent at 40 °C relative to poly­(methyl methacrylate) standards. b The crystallinity X c was calculated from DSC by dividing Δ H m = 19.3 J/g with Δ H m,100% = 219 J/g of DAD as crystallinity was caused by the addition of DAD. The Δ H m,100% of DAD was estimated by interpolation from the Δ H m,100% of 1,12-diaminododecane and 1,6-hexamethylene diamine c The crystallinity X c was calculated from WAXS by using the deconvolution method to estimate the area of the amorphous and crystalline portions.…”
Section: Resultsmentioning
confidence: 99%
“… b The crystallinity X c was calculated from DSC by dividing Δ H m = 19.3 J/g with Δ H m,100% = 219 J/g of DAD as crystallinity was caused by the addition of DAD. The Δ H m,100% of DAD was estimated by interpolation from the Δ H m,100% of 1,12-diaminododecane and 1,6-hexamethylene diamine …”
Section: Resultsmentioning
confidence: 99%
“…When OUa, TA and TAEA reacted together, the absorption bands of the PUIs formed (OUa 3 -T 2 , OUa 1 -T 1 and OUa 2 -T 3 ) were similar to those of OUa 1 -T 0 . The broad N-H stretching vibrations indicated the wide distribution of ordered and disordered hydrogen bonds (difference in distance and geometry), 59,60 which was also confirmed by the broad band due to CvO stretching vibrations, including free urea bonds. In addition, the adsorption at 1633 cm −1 suggested that the hydrogen bonds were mostly in a disordered form in PUIs.…”
Section: Synthesis and Characterization Of Poly(urea-imine) Thermosetsmentioning
confidence: 72%
“…Zhao and coworkers developed a catalyst‐free two‐step method to synthesize CO 2 ‐based PUrs to improve the properties 18 . Nevertheless, high pressure and long reaction time are required for this method, which hinders further development in the commecilization 19,20 . The synthetic method based on dicarbamates and diamine also seems quite attractive but catalysts are usually required 21 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Nevertheless, high pressure and long reaction time are required for this method, which hinders further development in the commecilization. 19,20 The synthetic method based on dicarbamates and diamine also seems quite attractive but catalysts are usually required. 21 In this method, a two-step procedure is more favorable than a one-pot procedure.…”
Section: Introductionmentioning
confidence: 99%